WALL-E [videorecording (DVD)] - Stanton, Andrew; Burtt, Ben; Knight, Elissa; Garlin, Jeff, 1962- (Walt Disney Home Entertainment, 2008)
After hundreds of lonely years, a waste management robot finds a new purpose in life. With only a cockroach for a friend, he finds true love in another robot sent on a mission to Earth to see if it is safe for human life.